Reimagining Positive Youth Development and Life Skills in Sport Through a Social Justice Lens - Camiré, Martin; Newman, Tarkington J.; Bean, Corliss; Strachan, Leisha (Université d'Ottawa | University of Ottawa, 2022)
Since the early 2000s, models of positive youth development (PYD), as well as the concept of life skills, have served as popular approaches by which to situate psychosocial development in youth sport research. However, critiques have been put forth in terms of how the PYD approach fails to address power, privilege, and oppression and how life skills do not fully encompass the wide range of learning outcomes that can arise from sport participation. In light of social justice issues (e.g., systemic racism, gender inequity) that have led citizens in many countries to mobilize for change, there is a need to explore how PYD and life skills can be reimagined in order for youth sport research to be better positioned to promote dialogue and action on social justice issues in youth sport. The purpose of the present paper is to reimagine PYD and life skills in sport through a social justice lens. Following reflections on how PYD and life skills can be framed to further promote social justice in youth sport, implications for practice and research are offered.
Keywords: advocacy; activism; coach education; athletes; social change